1982
DOI: 10.1002/jmor.1051730106
|View full text |Cite
|
Sign up to set email alerts
|

Setiferous structures of male coleoptera

Abstract: A scanning electron microscopy study was made of the male setiferous sex patches and analogous structures in 11 families of Coleoptera (Anthribidae, Bruchidae, Ciidae, Cleridae, Coccinellidae, Dermestidae, Leiodidae, Ptinidae, Staphylinidae, Tenebrionidae, and Ostomatidae). These secondary sexual characters appear to have several features in common including relatively long, often ridged, setae, cuticular ducts (frequently cribriform pore plates), and the production of a secretion. It is suggested that these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 18 publications
1
22
0
1
Order By: Relevance
“…Their basic structure, comprising a depression-containing dense, fluted or grooved setae, and numerous pores, is similar to that found in the setiferous sex patches of other Coleoptera (Faustini & Halstead, 1982).…”
Section: Discussionmentioning
confidence: 55%
“…Their basic structure, comprising a depression-containing dense, fluted or grooved setae, and numerous pores, is similar to that found in the setiferous sex patches of other Coleoptera (Faustini & Halstead, 1982).…”
Section: Discussionmentioning
confidence: 55%
“…Ma et al 1980;Bartelt et al 1993). There are no special structures on the male's surface to release the pheromone (as in other Coleoptera, see Faustini & Halstead 1982). Due to the wetting properties of isopropyl esters (Oodyke 1976;Dettner 1984), it might simply spread over the entire surface during release.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, a hypothesis is that the sclerolepidia are part of a secretory system, the function of the secretion being unknown. Faustini & Halstead (1982) noted the presence of pores adjacent to setae of setiferous sex patches in male Coleoptera. They demonstrated that these pores were the orifices of secretory cells, and provided images of a waxy secretion being produced from such a pore.…”
Section: Functionmentioning
confidence: 98%